Application of an improved firework algorithm for simultaneous estimation of temperature-dependent thermal and optical properties of molten salt. (October 2016) - Ren, Ya-Tao; Qi, Hong; He, Ming-Jian; Ruan, Shi-Ting; Ruan, Li-Ming; Tan, He-Ping
Abstract: Accurate measurement of the thermal and optical properties of molten salt is important in harvesting of solar energy. In this study, a secondary optimization technique that can be used to simultaneously retrieve the temperature-dependent absorption coefficient and the thermal conductivity of molten salt was proposed. The forward coupled radiation–conduction problem in a participating slab exposed to a pulse laser was solved by the finite volume method. An improved firework algorithm (FWA) was introduced to solve inverse problems, which was proven to be more efficient and robust than the original FWA and particle swarm optimization. All research outcomes indicated that the thermal and optical properties of high-temperature molten salt could be retrieved accurately by the proposed secondary optimization technique from the optical and thermal measurement signals.